Comanagement Strategy Between Academic Institutions and Community Practices to Reduce Induction Mortality in Acute Promyelocytic Leukemia. Issue 4 (April 2021) - Jillella, Anand P.; Arellano, Martha L.; Gaddh, Manila; Langston, Amy A.; Heffner, Leonard T.; Winton, Elliott F.; McLemore, Morgan L.; Zhang, Chao; Caprara, Catherine R.; Simon, Kathryn S.; Bolds, Sheldon L.; DeBragga, Stephanie; et al.
Abstract : PURPOSE: Acute promyelocytic leukemia (APL) is a curable leukemia with > 90% survival in clinical trials. Population-based studies from Sweden and US SEER data have shown long-term survival rates of 62% and 65.7%, with the lower rate being from a higher percentage of early deaths. METHODS: In this prospective, multicenter trial, we developed a simplified algorithm that focused on prevention and early treatment of the three main causes of death: bleeding, differentiation syndrome, and infection. All patients with a diagnosis of APL were included. The initial 6 months were spent educating oncologists about early deaths in APL. At the time of suspicion of an APL, an expert was contacted. The algorithm was made available followed by discussion of the treatment plan. Communication between expert and treating physician was frequent in the first 2 weeks, during which time most deaths take place. RESULTS: Between September 2013 and April 2016, 120 patients enrolled in the study from 32 hospitals. The median age was 52.5 years, with 39% > 60 years and 25% with an age-adjusted Charlson comorbidity index > 4. Sixty-three percent of patients were managed at community centers. Two patients did not meet the criteria for analysis, and of 118 evaluable patients, 10 died, with an early mortality rate of 8.5%. With a median follow-up of 27.3 months, the overall survival was 84.5%. CONCLUSION: Induction mortality can be decreased and population-wide survival improved in APL with the use of standardized treatment guidelines. Support from experts who have more experience with induction therapy is crucial and helps to improve the outcomes.